IoT based Biotelemetry for Smart Health Care Monitoring System (Journal of Information Technology and Digital World, 2020)
The concept of biotelemetry evolved to assess the physiological data of a person under normal circumstances without obstruction to the patient. It allows evaluation of risk factors influence the person health on their daily activities. Recent technology development enhances the features of biotelemetry as wireless applications which allows the physician to monitor the patient health remotely. Biotelemetry obtains great values in hospitals by continues monitoring process as it reduces the burden to physician regular checkups. ECG telemetry is one of the predominant biotelemetry application employed to monitor the heart rate and arrhythmias. Proposed research work focusses the key features of ECG telemetry and provides an internet of things (IoT) based application to monitor the patient health in an indoor and outdoor environment. Along with medical terms, data management parameters are analyzed in the experimental section to emphasize the proposed work performance.
Keywords: Electrocardiogram (ECG); Biotelemetry; Internet of Things (IoT)